2011
DOI: 10.5301/hip.2011.7422
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dysplasia in Femoroacetabular Impingement

Abstract: It is unknown how often femoro-acetabular impingement (FAI) and hip dysplasia co-exist and which is more important in the development of intra-articular lesions such as labral tears. This study identified the prevalence of dysplasia on standard radiographs in a group of 76 consecutive patients with symptomatic FAI. The centre-edge (CE) angle of Wiberg, the acetabular angle (AA) of Sharp, FAI type, offset ratio and posterior wall sign were identified. 63 patients, predominantly young adult males (mean age: 34.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…We also found that patients with cam-type FAI and concomitant low lateral center-edge angles or high Tönnis angles (both representing acetabular dysplasia) were at increased risk of osteoarthritis progression. Co-occurrence of acetabular dysplasia and FAI has been documented previously with authors positing that the combination increases the risk of intraarticular pathology [2,6,11,12,16]. Tannast and colleagues [20] recently published modified reference values for acetabular overcoverage and undercoverage based on a cohort managed with hip preservation surgery, postulating that previous cutoffs may not provide optimal accuracy.…”
Section: Discussionmentioning
confidence: 97%
“…We also found that patients with cam-type FAI and concomitant low lateral center-edge angles or high Tönnis angles (both representing acetabular dysplasia) were at increased risk of osteoarthritis progression. Co-occurrence of acetabular dysplasia and FAI has been documented previously with authors positing that the combination increases the risk of intraarticular pathology [2,6,11,12,16]. Tannast and colleagues [20] recently published modified reference values for acetabular overcoverage and undercoverage based on a cohort managed with hip preservation surgery, postulating that previous cutoffs may not provide optimal accuracy.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, other authors have reported that radiological FAI findings do not lead to the development of significant OA [31][32][33]. Paliobeis et al [34] emphasized that the presence of coexisting developmental dysplasia of the hip should be taken into account for the treatment of patients with FAI. The issue of whether FAI is a risk factor for the development of hip OA remains controversial.…”
Section: Figmentioning
confidence: 97%
“…Thus, identifying anatomic factors that compensate for or exacerbate FAI or instability is important when treating young patients with hip pain. Femoral and acetabular retroversion are known to exacerbate or contribute to impingement [16,25,28,43,48], while femoral and acetabular anteversion may exacerbate mild underlying Values are expressed as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%